Letter - González, Marcelino
025a-0130-001 London, 16th March, 1939. Secretary of Trades Union Transport House, Greatsmith Square, S. W. 1 Dear Sir, Further to our last letter, we beg to inform you that for an involuntary omission we left out of the list the two members, Captain and Officer of the s/s. "Sabina", Mr. Aurelio Benito and Mr. Jaime Moscoso. We referred to these gentlemen in our conversation in our last call on you, and we shall be glad if you will consider them included for any benefits that you should kindly get for them. Yours faithfully, Marcelino González. 292/946/25a/130